High HMGA2 expression without gene rearrangement in meningiomas. Issue 6 (18th August 2020) - Nagaishi, Masaya; Nakae, Ryuta; Matsumoto, Yoshiyuki; Fujii, Yoshiko; Sugiura, Yoshiki; Takigawa, Tomoji; Suzuki, Kensuke
Abstract : High mobility group AT‐hook 2 (HMGA2) is a non‐histone transcriptional regulator protein. Aberrant expression of the HMGA2 gene ( HMGA2 ) and structural rearrangement at the chromosomal region 12q14 with HMGA2 involvement have been reported in several mesenchymal tumors. We analyzed truncated and full‐length HMGA2 expression in 55 cases of meningioma, the most common brain tumor of mesenchymal origin. Fluorescence in situ hybridization and 3′‐rapid amplification of cDNA ends were used to investigate the possibility of gene rearrangements. Moreover, the relationship between HMGA2 expression and clinicopathological features was assessed. Compared with normal brain tissues, 95% of the meningioma tissues exhibited increased HMGA2 expression. In 14 cases, the expression of truncated HMGA2 was more than two‐fold higher than that of paired full‐length HMGA2 . Chromosomal translocation involving the chromosomal region 12q14 was undetectable. No significant correlation was found between the Ki‐67 labeling index and HMGA2 expression and between the HMGA2 expression and the clinicopathological features. The majority of the meningioma cases displayed increased HMGA2 expression, which was not attributed to the chromosomal rearrangement at the corresponding region. Similar to that in the other mesenchymal tumors, increased HMGA2 expression was not associated with tumor cell proliferation in meningiomas.